Specyfika sprzedaży energii elektrycznej a controlling sprzedaży - Iwaniec, Magdalena Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper discusses sales controlling (as a conception which supports sales management) against the background of the peculiarity of sale's electricity. The author tries to answer the question whether sales controlling can be used in the distribution company (DisCo). (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1178, s. 39-48